Potential Utilization of Local History Materials throught Analysis of History Learning Outcomes in High Schools in the Independent Curriculum - Hafida, Mellina Nur; Agung, Dewa Agung Gede; Widiadi, Aditya Nugroho (UNIVERSITAS MUHAMMADIYAH METRO, 2025)
Local history in an area can be used as part of the learning material. Effective strategies and approaches in aligning local history materials with learning needs at the high school level are part that needs to be studied. The study of history learning in the context of the Merdeka curriculum provides opportunities for educators to present history materials in a local context. This study aims to explore the potential use of local history materials in the analysis of history learning outcomes in high school by implementing the Independent curriculum using a descriptive qualitative method through literature studies. The main focus of the research is on the application of local history potential in history learning materials, with the belief that each region has its unique potential and historical studies. The results of this study contribute to the development of history teaching methods that are more contextual and relevant to local reality.